Offensive process analysis in handball: Identification of game actions that differentiate winning from losing teams - Ferrari, W. R.; Valente-dos-Santos, J.; Simões Vaz, V. P. (American Journal of Sports Science, 2014)
This present study aims to show the main offensive differences between handball teams that lead to a win or a loss. The samples were collected through quantitative analyses of the Champions League 2011-2012 handball games. This study relied on non-descriptive and non-parametric statistics. The Mann-Whitney U test was used as the statistical method. The variables that show the significant differences in favour of the winners were the goals obtained in positioned attacks, 9-meter goals and 7-meter penalties, which, in the semi-finals and final decided who the winner would be. This study shows that the teams who reached the finals and came out victorious have a wide and well-defined range of offensive actions enabling them to involve all aspects of the game, in any situation. This tendency was particularly visible in positioned attacks, which was the main difference throughout the competition.